(untitled) (Bangladesh Journal of Botany, 2022)
Chitosan, as a carrier of Bacillus amyloliquefaciens, is a biological edible film used to control the post harvest disease of Fuji apples. After coating the apples with chitosan, the preservation of Fuji apples in post harvest storage was measured by testing the weightless and decay rates; hardness; malondialdehyde (MDA), soluble solids (SS), titratable acid (TA), and Vitamine C (VC) contents; and all kinds of changes in oxidase activity (e.g., peroxidase, superoxide dismutase, and catalase). Results showed that the biological edible film can reduce the weightless and decay rates of the apples effectively, control the increase in MDA, and decrease TA, VC, and SS contents. These results indicated a good fresh-keeping effect. Bangladesh J. Bot. 51(1): 65-73, 2022 (March)